Alkali-sulfate-aluminum salt ternary composite excitation cementing material and application thereof
By introducing aluminum salt into the alkali-sulfate binary excitation slag, the alkali-sulfate-aluminum salt ternary composite excitation gelling material is formed, which solves the problem of limited growth in the mine filler strength and achieves efficient filler strength Boost and durability enhancement.
Patent Information
- Application Number
- CN202411489727.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
AI Technical Summary
Among existing mine filling materials, the strength growth of alkali-sulfate composite excitation slag-based filling bodies is limited by the high free water content and porosity, which is difficult to meet the demand for high-strength filling.
Aluminum salt is introduced as the third-party excitation material based on alkali-sulfate binary excitation slag, optimize the ratio of gelling materials, and form alkali-sulfate-aluminum salt ternary composite excitation gelling materials, including blast furnace slag micro powder, Sulfate and alkaline exciters, and promote hydration reactions through aluminum salt admixtures, to produce hydrated calcium silicate gels and ettringite, reducing porosity and free water content.
It significantly improves the compressive strength of the filling body, shortens the settling time, enhances the resistance to acid erosion and carbonization oxidation, and improves the durability of the filling body and the mine filling efficiency.
Smart Images

Figure CN119263666A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mine filling materials, and in particular relates to an alkali-sulfate-aluminum salt ternary composite activated gelling material and application thereof. Background Art
[0002] The tailings cementing filling technology currently widely used in mines transports a composite material composed of tailings, binder and water into the mine and solidifies it to fill the goaf. This technology can control ground pressure while reducing tailings accumulation, reduce surface settlement, and solidify heavy metal ions, reducing land reclamation costs. As one of the important components of filling materials, binder provides the bonding force between tailings particles, so it is a decisive factor in the strength and stability of the filling body. At the same time, the hydration generated by the binder after hydration can solidify some heavy metals through chemical bonding or physical adsorption, thereby reducing the impact of void filling on the underground environment.
[0003] Ordinary Portland cement has been used as the main binder for mine filling due to its stable performance and wide sources. However, as a cementitious material, it still has problems such as insufficient filling strength, susceptibility to sulfate erosion, high filling cost, and high carbon emissions during the production process. Therefore, it is crucial to find an alternative solution with better performance, lower cost and more environmental protection.
[0004] In recent years, granulated blast furnace slag (hereinafter referred to as slag) has attracted the attention of scholars and engineers at home and abroad due to its wide source, low cost and good pozzolanic activity. When slag is in an alkaline environment, it can generate hydration products with gelling effect through reaction, which shows that slag has the potential to be a new type of cementitious material. Mine filling slag-based cementitious materials can be divided into three types: cement-slag mixture, alkali-activated slag, and alkali-sulfate composite activated slag.
[0005] Cement-slag mixture is made by adding slag to cement to partially replace cement. The amount of slag added is generally not more than 50%. Since the activity of slag needs to be stimulated in the alkaline solution formed by cement hydration, and as the slag content increases, the cement content continues to decrease, and the alkalinity of the solution continues to weaken, resulting in the inability to fully stimulate the slag activity. Therefore, the early strength of the filling body with a high slag replacement rate will decrease. At present, cement-slag mixture is rarely used in the field of mine filling.
[0006] Alkali-activated slag uses alkaline activators to break the silicon-oxygen bonds in the glass network of the slag and then condense to form hydrated aluminum silicate gel to produce gelation. It has the advantages of good fluidity, low hydration heat, high strength and strong corrosion resistance, but it is only suitable for high-concentration filling materials, with high cost, strong corrosiveness and complex processing technology.
[0007] Compared with the above two types of slag-based cementitious materials, alkali-sulfate composite activated slag combines sulfate activated and alkali activated slag, and its main components include slag, sulfate activator and alkaline activator. It has the advantages of wide source of raw materials, low cost, good fluidity, low hydration heat and high strength. It has become the most commonly used slag-based cementitious material and has broad development prospects.
[0008] There are currently a number of invention patents on alkali-sulfate composite activated slag technology in the prior art. Patent CN107365094A discloses a method for preparing a mine filling slurry, which uses blast furnace slag, quicklime, desulfurized gypsum, cement clinker and mirabilite to prepare tailings cementitious material, in which the blast furnace slag content is about 90%. In the embodiment with a ash-sand ratio of 1:8 and a concentration of 75%, the strength at 7 days and 28 days is 0.7MPa and 1.9MPa, which is difficult to meet the requirements of high-strength filling work.
[0009] Patent CN113248225A discloses a mine filling cementitious material, which uses slag, fly ash, gypsum, clinker, lime and activator to prepare the cementitious material. In the best strength performance of Example 2:3# test, under the condition of ash-sand ratio of 1:10 and concentration of 70%, the strength of the filling body at 7d, 28d and 56d was 2.67MPa, 4.65MPa and 4.98MPa respectively. The long-term strength growth is not obvious, and there is still a lot of room for improvement.
[0010] The strength of the filling body will increase as its internal free water content and porosity decrease. However, in order to achieve the purpose of pipeline or gravity conveying filling slurry, the water-cement ratio of the filling slurry (usually 3-8) is greater than the water-cement ratio of cement paste / mortar / concrete (usually 0.4-0.6), resulting in a high free water content and porosity of the filling body even at a later age, which restricts the further growth of the filling body strength. Therefore, if more hydration products can be generated to fill the pores to reduce the porosity while reducing the free water content, the strength of the filling body can be significantly improved.
[0011] Studies have shown that the addition of aluminum salts can promote the hydration reaction in the alkali-sulfate composite excitation system, consume a large amount of free water and increase the yield of the hydration products hydrated calcium silicate gel and ettringite. Among them, hydrated calcium silicate gel has a strong gelling ability, and ettringite can fill the pores in the filling body. The increase in the production of both can significantly improve the compressive strength of the filling body.
[0012] Therefore, based on the alkali-sulfate binary activated slag, the present invention innovatively introduces aluminum salt as the third activated material, and optimizes and determines the optimal ratio of cementitious materials to solve the problem that the high free water content and porosity of mine slag-based filling bodies restrict further strength growth. Summary of the invention
[0013] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an alkali-sulfate-aluminum salt ternary composite activated slag filling cementitious material, most of the raw materials of which are solid waste materials. While solving the problem of solid waste in mines, a cementitious material with excellent performance is provided.
[0014] In order to achieve the above technical objectives, this application adopts the following technical solutions:
[0015] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 65-80 parts of blast furnace slag powder, 20-30 parts of sulfate, 5-10 parts of alkali and 0.5-5 parts of aluminum salt admixture.
[0016] The blast furnace slag powder is obtained by grinding granulated blast furnace slag used in blast furnace ironmaking or crude steelmaking, and its specific surface area is not less than 350m 2 / kg.
[0017] The sulfate is an inorganic salt containing sulfate radicals and is composed of any one or more of natural gypsum, phosphogypsum, fluorgypsum, citric acid gypsum, desulfurized gypsum, anhydrite or analytically pure calcium sulfate.
[0018] The alkali is any one of quicklime, slaked lime, hydrated lime, carbide slag, calcium hydroxide or sodium hydroxide, or a combination of the two.
[0019] The aluminum salt additive is a compound or mixture containing soluble aluminum salt, including any one or more of diabase, alunite, aluminum sulfate, aluminum nitrate and aluminum chloride.
[0020] Further, the alkali-sulfate-aluminum salt ternary composite activated cementitious material is composed of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide content, and 3 parts of aluminum salt admixture;
[0021] Alternatively, the following components are used, by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide, and 2 parts of aluminum salt admixture.
[0022] Alternatively, the invention is composed of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide and 5 parts of aluminum salt admixture.
[0023] Furthermore, the basicity coefficient (CaO+MgO) / (SiO2+Al2O3) of the blast furnace slag powder is not less than 1.0, and the hydration coefficient (CaO+MgO+Al2O3) / SiO2 is not less than 1.4.
[0024] Furthermore, the sulfate is anhydrite with a CaO and SO3 content of more than 80%, and the powdered alkaline activator is calcium hydroxide with a purity of more than 80%.
[0025] Furthermore, the aluminum salt additive is required to have an industrial purity of more than 80%.
[0026] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0027] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1: (6-12), mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 67%-77%, that is, the slurry water content of 23wt%-33wt%, add it into the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0028] The 3-day uniaxial compressive strength of the prepared filling slurry is ≥1.2MPa, which is ≥70% higher than that of cement filling and ≥50% higher than that of alkali-sulfate binary activated filling; the 7-day uniaxial compressive strength is ≥3.5MPa, which is ≥160% higher than that of cement filling and ≥90% higher than that of alkali-sulfate binary activated filling; the 28-day uniaxial compressive strength is ≥6.4MPa, which is ≥200% higher than that of cement filling and ≥160% higher than that of alkali-sulfate binary activated filling; the 56-day uniaxial compressive strength is ≥6.9MPa, which is ≥180% higher than that of cement filling and ≥130% higher than that of alkali-sulfate binary activated filling.
[0029] The working principle of the present invention is as follows: in terms of hydration mechanism, the aluminum salt admixture will dissolve and release a large amount of aluminum ions after being added to water. When hydrated calcium silicate gel and calcium sulfonate are generated, aluminum ions and calcium ions in the solution will be consumed, resulting in a decrease in the concentration of the two, further leading to an undersaturated state of the slag, and promoting further dissolution of the slag; at the same time, the decrease in calcium ion concentration also promotes the dissolution of calcium hydroxide, releasing a large amount of hydroxide ions, thereby enhancing the alkalinity of the solution, and further promoting the breaking of Si-O bonds in the slag. The combined influence of these effects promotes the hydration of the slag, increases the hydration rate of the filling body, increases the output of the hydration products hydrated calcium silicate gel and calcium sulfonate, consumes more free water, forms a denser microstructure, and improves the uniaxial compressive strength of the filling body.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The ternary composite activated cementitious material can reduce the porosity and free water content of the filling body, significantly improving the compressive strength of the filling body compared with the cement filling body and alkali-sulfate binary activated filling body under the same conditions. At the same time, it can shorten the setting time, increase the early strength, and significantly improve the mine filling efficiency.
[0032] (2) The ternary composite activated cementitious material reduces the porosity of the filling, making the filling more dense, enhancing the filling's ability to resist acid erosion, sulfate erosion, and oxidation carbonization, and improving the durability of the filling material.
[0033] (3) The main materials of the ternary composite activated cementitious material prepared by the present invention are industrial waste or by-products. While maintaining the advantages of the traditional alkali-sulfate binary composite activated filling body, the main materials are widely available, low cost, and simple structure. At the same time, the third component aluminum salt admixture introduced has a small dosage, low cost, and a wide source. After addition, it has little effect on the fluidity of the filling slurry. Therefore, a significant increase in the strength of the filling body can be achieved without significantly increasing the filling cost and the complexity of the preparation and filling process. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The relationship diagram of the alkali-sulfate-aluminum salt ternary composite excitation reaction of the present invention;
[0035] Figure 2 In Example 1-3 of the present invention, a scanning electron microscope image of the filling body at a curing age of 56 days;
[0036] Figure 3 In Comparative Example 1-2 of the present invention, a scanning electron microscope image of the filling body at a curing age of 56 days. DETAILED DESCRIPTION
[0037] In the embodiment of the present invention, the blast furnace slag powder used is blast furnace slag powder obtained by grinding granulated blast furnace slag used in blast furnace ironmaking or smelting crude steel, and its specific surface area is 880m 2 / kg; the tailings used are mainly composed of quartz sand.
[0038] In the embodiment of the present invention, the basicity coefficient (CaO+MgO) / (SiO2+Al2O3) of the blast furnace slag powder used is 1.22, and the hydration coefficient (CaO+MgO+Al2O3) / SiO2 is 2.04.
[0039] In the embodiment of the present invention, the sulfate used is anhydrite, and the CaO and SO3 contents thereof are 80.8%, and the powdered alkaline activator is analytically pure calcium hydroxide with a purity of 99%.
[0040] In the embodiment of the present invention, the aluminum salt admixture used is alum stone with an industrial purity of 90%.
[0041] The relationship diagram of the alkali-sulfate-aluminum salt ternary composite excitation reaction of the ternary composite excitation gelling material prepared by the present invention is as follows Figure 1 shown.
[0042] Example 1
[0043] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide and 3 parts of alunite.
[0044] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0045] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0046] Example 2
[0047] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide and 2 parts of alunite.
[0048] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0049] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0050] Example 3
[0051] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide and 5 parts of alunite.
[0052] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0053] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0054] In Examples 1-3, the scanning electron microscope image of the prepared filling body at the curing age of 56 days is as follows: Figure 2 shown.
[0055] Example 4
[0056] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 71 parts of blast furnace slag powder, 22 parts of anhydrite, 7 parts of calcium hydroxide and 5 parts of alunite.
[0057] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0058] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0059] Example 5
[0060] An alkali-sulfate-aluminum salt ternary composite activated cementitious material consists of the following components in parts by weight: 71 parts of blast furnace slag powder, 22 parts of anhydrite, 5 parts of calcium hydroxide and 4 parts of alunite.
[0061] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0062] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0063] Example 6
[0064] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 74 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide and 3 parts of alunite.
[0065] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0066] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0067] Example 7
[0068] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 71 parts of blast furnace slag powder, 28 parts of anhydrite, 5 parts of calcium hydroxide and 2 parts of alunite.
[0069] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0070] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0071] Example 8
[0072] An alkali-sulfate-aluminum salt ternary composite activated gelling material consists of the following components by weight: 74 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide and 3 parts of alunite.
[0073] The application of the alkali-sulfate-aluminum salt ternary composite activated gelling material is specifically used for preparing filling slurry, which includes the following steps:
[0074] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0075] Comparative Example 1
[0076] Using silicate cement as a single binder to prepare filling slurry includes the following steps:
[0077] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0078] Comparative Example 2
[0079] An alkali-sulfate composite activated gelling material consists of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite and 7 parts of calcium hydroxide.
[0080] The application of the alkali-sulfate composite activated gelling material is specifically used for preparing filling slurry, which comprises the following steps:
[0081] Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1:9, mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 77%, that is, the water content of the slurry is 23wt%, add it to the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
[0082] In Comparative Examples 1-3, the scanning electron microscope image of the prepared filling body at the curing age of 56 days is as follows: Figure 3 shown.
[0083] The test results of Examples 1-8 and Comparative Examples 1-2 are shown in Table 1 and Table 2:
[0084] Table 1 Uniaxial compressive strength of the filling bodies of the comparative examples and embodiments at 3d, 7d, 28d and 56d
[0085]
[0086] Table 2 Cumulative hydration heat, expansion and filling body porosity of filling slurries prepared in Examples 1-3 and Comparative Examples 1-2
[0087]
[0088]
Claims
1. An alkali-sulfate-aluminum salt ternary composite activated gelling material, characterized in that: The invention is composed of the following components by weight: 65-80 parts of blast furnace slag powder, 20-30 parts of sulfate, 5-10 parts of alkali and 0.5-5 parts of aluminum salt admixture.
2. The alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 1, characterized in that: The blast furnace slag powder is obtained by grinding granulated blast furnace slag used in blast furnace ironmaking or crude steelmaking, and its specific surface area is not less than 350m 2 / kg.
3. The alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 1, characterized in that: The sulfate is an inorganic salt containing sulfate radicals and is composed of any one or more of natural gypsum, phosphogypsum, fluorgypsum, citric acid gypsum, desulfurized gypsum, anhydrite or analytically pure calcium sulfate.
4. The alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 1, characterized in that: The alkali is any one of quicklime, slaked lime, hydrated lime, carbide slag, calcium hydroxide or sodium hydroxide, or a combination of the two.
5. The alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 1, characterized in that: The aluminum salt additive is a compound or mixture containing soluble aluminum salt, including any one or more of diabase, alunite, aluminum sulfate, aluminum nitrate and aluminum chloride.
6. The alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 1, characterized in that: The alkali-sulfate-aluminum salt ternary composite activated cementitious material is composed of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide content, and 3 parts of aluminum salt admixture; Alternatively, the following components are used, by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide, and 2 parts of aluminum salt admixture. Alternatively, the invention is composed of the following components by weight: 68 parts of blast furnace slag powder, 25 parts of anhydrite, 7 parts of calcium hydroxide and 5 parts of aluminum salt admixture.
7. The alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 1, characterized in that: The basicity coefficient (CaO+MgO) / (SiO2+Al2O3) of the blast furnace slag powder is not less than 1.0, and the hydration coefficient (CaO+MgO+Al2O3) / SiO2 is not less than 1.
4.
8. The alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 1, characterized in that: The sulfate is anhydrite with a CaO and SO3 content of more than 80%, the powdered alkaline activator is calcium hydroxide with a purity of more than 80%; and the aluminum salt admixture is required to have an industrial purity of more than 80%.
9. The use of an alkali-sulfate-aluminum salt ternary composite activated gelling material as claimed in claim 1, characterized in that: Specifically, the method is used to prepare the filling slurry, comprising the following steps: Weigh the raw materials according to the cementitious material: tailings ash-sand ratio of 1: (6-12), mix and stir them evenly, then weigh the mixing water according to the mass concentration of the prepared slurry of 67%-77%, that is, the slurry water content of 23wt%-33wt%, add it into the mixed dry material for preliminary stirring, and then use a mixer to stir and mix evenly to obtain a filling slurry.
10. The use of an alkali-sulfate-aluminum salt ternary composite activated gelling material according to claim 9, characterized in that: The 3-day uniaxial compressive strength of the prepared filling slurry is ≥1.2MPa, which is ≥70% higher than that of cement filling and ≥50% higher than that of alkali-sulfate binary activated filling; the 7-day uniaxial compressive strength is ≥3.5MPa, which is ≥160% higher than that of cement filling and ≥90% higher than that of alkali-sulfate binary activated filling; the 28-day uniaxial compressive strength is ≥6.4MPa, which is ≥200% higher than that of cement filling and ≥160% higher than that of alkali-sulfate binary activated filling; The 56-day uniaxial compressive strength is ≥6.9MPa, which is ≥180% higher than that of cement filling and ≥130% higher than that of alkali-sulfate binary activated filling.
Citation Information
Patent Citations
Preparation method for filling slurry used for mine
CN107365094A
Mine filling cementing material
CN113248225A
Gypsum system excited composite cementing material and preparation method thereof
CN111377626A
Method for filling underground goaf of non-ferrous metal mine, method for treating tailing slurry of non-ferrous metal mine and biomass-based cementing material
CN114183192A
Low-carbon high-strength Portland slag cement as well as preparation method and application thereof
CN116621476A